Pengaruh Profitabilitas, Leverage dan Reputasi Kantor Akuntan Publik Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan: (Studi Empiris Pada Perusahaan Properties & Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2022) - Utami, Putu Dhea Apriyanti; Erlina Wati, Ni Wayan Alit; Padnyawati, Kadek Dewi (Hita Akuntansi dan Keuangan, 2024)
The Indonesian Stock Exchange requires prompt financial report submissions from all publicly traded companies. Financial reports must be submitted on time in order to provide meaningful information. The purpose of this study is to examine the relationship between the reliability of financial reporting times for property and real estate businesses listed on the Indonesia Stock Exchange from 2019 to 2022 and the following factors: profitability, leverage, and the reputation of the public accounting firm. Using purposive selection, this quantitative study draws from a pool of 57 different businesses. This study makes use of logistic regression analysis for its statistical data. The study found that profitability is a positive attribute that affects financial reporting time accuracy. At the same time, the public accounting firm’s reputation and leverage are irrelevant to the performance of financial reports.